UNIT 23.7 Middle‐Down and Top‐Down Mass Spectrometric Analysis of Co‐occurring Histone Modifications. (1st August 2014) - Molden, Rosalynn C.; Garcia, Benjamin A.
Abstract: Histones are chromatin proteins that are highly modified with many different types of post‐translational modifications. These modifications act in concert to regulate a number of chromatin‐related processes. However, identification and quantification of co‐occurring histone post‐translational modifications is challenging because there are many potential combinations of modifications and because the commonly used strategy of fragmenting proteins using trypsin or an alternative protease prior to LC‐MS/MS analysis results in the loss of connectivity between modifications on different peptides. In this unit, mass spectrometric methods to analyze combinatorial histone modifications on histone tails (middle‐down mass spectrometry) and on intact histones (top‐down mass spectrometry) are described. Curr. Protoc. Protein Sci . 77:23.7.1‐23.7.28. © 2014 by John Wiley & Sons, Inc.